2022
DOI: 10.1002/adma.202109426
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Tailored Surface Oxide on Cu–Ga Intermetallics Enhances CO2 Reduction Selectivity to Methanol at Ultralow Potential

Abstract: Electrochemical CO2 reduction reaction (eCO2RR) is performed on two intermetallic compounds formed by copper and gallium metals (CuGa2 and Cu9Ga4). Among them, CuGa2 selectively converts CO2 to methanol with remarkable Faradaic efficiency of 77.26% at an extremely low potential of −0.3 V vs RHE. The high performance of CuGa2 compared to Cu9Ga4 is driven by its unique 2D structure, which retains surface and subsurface oxide species (Ga2O3) even in the reduction atmosphere. The Ga2O3 species is mapped by X‐ray p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 65 publications
0
51
0
Order By: Relevance
“…Figure 4d shows that there is an interesting correlation of bond distances between the experimental real-time observation via extended X-ray absorption fine structure (EXAFS) analysis and computationally optimized structure analysis. 34 Figure 4e shows the data comparison of Pd 3d XPS for Pt 0.2 Pd 1.8 Ge before and after 50,000 ADT cycles of the ORR.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure 4d shows that there is an interesting correlation of bond distances between the experimental real-time observation via extended X-ray absorption fine structure (EXAFS) analysis and computationally optimized structure analysis. 34 Figure 4e shows the data comparison of Pd 3d XPS for Pt 0.2 Pd 1.8 Ge before and after 50,000 ADT cycles of the ORR.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…55 The real-time in situ XAS study has also been performed at a different time interval to see the electronic structural evolution and charge transfer kinetics between Pd and In in spite of the catalysts. 56,57 The time-dependent XANES spectra of the In K-edge of PdIn@In 2 O 3 sample at −0.9 V potential show that the white line intensity for In decreases, indicating the increase in the electron density on the In site as CO 2 RR progresses (Figure S15a). During the CO 2 RR structure, the bond distance corresponding to In−O bond does not change much, as presented in Figure S15b.…”
Section: Resultsmentioning
confidence: 99%
“…KCl) in 0.5 M KHCO 3 . Recently, Bagchi et al 192 reported excellent selectivity towards methanol could be achieved with an intermetallic 184 Copyright 2019, the American Chemical Society. Source: https://pubs.acs.org/doi/10.1021/ jacs.9b10709.…”
Section: Highly Reduced C 1 Productsmentioning
confidence: 99%
“…KCl) in 0.5 M KHCO 3 . Recently, Bagchi et al 192 reported excellent selectivity towards methanol could be achieved with an intermetallic CuGa 2 electrocatalyst. An exceptional FE of 77.6% for methanol was achieved at −0.3 V vs .…”
Section: Copper Alloys For Selective Reduction Of Co2mentioning
confidence: 99%